An antibacterial UV coating and its application in decorative panels

By using calcium carbonate whiskers loaded with antibacterial agents and coated with modified chitosan antibacterial composite materials in UV coatings, the problems of insufficient antibacterial performance and poor antibacterial durability of existing UV coatings are solved, and efficient antibacterial effect and good water and oil resistance are achieved.

CN119242164BActive Publication Date: 2025-03-21寿光市鲁丽木业股份有限公司 +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411793395.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-21
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

During the application process, existing UV coatings have insufficient antibacterial performance, poor antibacterial durability, poor water and oil resistance, and easy loss of antibacterial agents, affecting adhesion and binding firmness.

Method used

Antibacterial UV coating formulations are made using parts by weight, including polyurethane acrylates, monomers, antibacterial composites, modified polysilazanes and photoinitiators. The antibacterial composite material is loaded with antibacterial agents through calcium carbonate whiskers and coated with modified chitosan to delay the sustained release of antibacterial agents and improves antibacterial durability.

Benefits of technology

The antibacterial properties and durability of UV coatings have been significantly improved. The antibacterial rates of E. coli and Staphylococcus aureus have reached 99.92%-99.99%, water and oil resistance have been improved, the water contact angle has reached 122.6°-123.4°, oil pollution resistance has reached 99.4%-99.7%, and the adhesion strength is high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses an antibacterial UV coating and its application in a decorative panel, belonging to the technical field of coating compositions, wherein the antibacterial UV coating comprises the following raw material components by weight: 40-50 parts of polyurethane acrylate, 42-48 parts of monomer, 1-2 parts of antibacterial composite material, 5-8 parts of modified polysilazane, and 2-3 parts of photoinitiator. The antibacterial UV coating of the invention has excellent antibacterial performance, and the antibacterial rate of Escherichia coli and Staphylococcus aureus reaches 99.92%-99.99%, and has high antibacterial persistence. After 100h of ultraviolet light irradiation, the antibacterial rate of Escherichia coli and the antibacterial rate of Staphylococcus aureus are still higher than 95%; the antibacterial UV coating of the invention has high water and oil resistance and high adhesion strength, the water contact angle is 122.6°-123.4°, the oil resistance reaches 99.4%-99.7%, and the adhesion on the wood test plate is 0 grade.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating compositions, and in particular relates to an antibacterial UV coating and application thereof in decorative panels. Background Art

[0002] Veneer is a type of board used for interior decoration, used to cover and beautify the internal structure of a building. There are many types of veneers, including wood veneers (such as solid wood, artificial boards, wood-plastic, etc.), metal veneers, gypsum veneers, glass veneers, plastic veneers, etc. In addition, according to different surface treatment methods, there are also many types such as paint-free, molded, double veneer, solid wood veneer, UV paint finishing, etc.

[0003] After the surface of the veneer is treated with UV paint photocuring protection, it has the advantages of smoothness, wear resistance, scratch resistance, strong chemical resistance and long service life. However, the UV coating on the veneer will come into contact with different types of bacteria during the application process. Under suitable conditions, the bacteria will multiply in large numbers, destroying the original properties of the coating and seriously reducing the quality. In addition, with the improvement of hygiene requirements, medical equipment, oil storage, children's toys and furniture and other fields have also put forward antibacterial and antimicrobial requirements for the UV coating of veneers.

[0004] In order to improve the antibacterial performance of UV coatings, inorganic antibacterial agents or low molecular organic antibacterial agents are often used in the prior art. CN101338087B discloses an antibacterial UV coating and its production process. In the process, nano silver powder and a wetting dispersant are first mixed to form an antibacterial stock solution, and then the antibacterial stock solution is mixed with polyester acrylate in the UV coating to form an antibacterial mother solution. Finally, the antibacterial mother solution is mixed with other components of the UV coating to form the antibacterial UV coating. The nano silver powder mixed and dispersed in the polyester acrylate can be well dispersed in the UV coating. V coating, so that the antibacterial UV coating has good antibacterial and bactericidal properties, and can kill bacteria attached to the coating by itself; CN112574608A discloses an antibacterial coating for interior decoration and a preparation method thereof, the antibacterial coating is composed of hydroxy acrylic resin, titanium dioxide, dispersant, anti-settling agent, leveling agent, antibacterial agent, isocyanate curing agent, the antibacterial agent is an inorganic silver ion antibacterial agent and an organic benzothiazolinone. In addition to having excellent physical and chemical properties, the antibacterial coating for interior decoration also has excellent antibacterial and antifungal properties.

[0005] When nanosilver or silver ions are used as antibacterial materials, not only is the production cost high, but the antibacterial nanosilver powder or silver ions on the coating surface are easily lost after long-term friction, affecting the antibacterial durability; when organic benzothiazolinone low-molecular organic antibacterial agents are used as antibacterial materials, the antibacterial agents are easy to escape from the coating, affecting the antibacterial rate and antibacterial durability. In addition, when UV coatings are applied to decorative panels, the inorganic antibacterial agents or organic antibacterial agents directly contact the surface of the decorative panels, reducing the adhesion between the coating and the decorative panels, and reducing the firmness of the combination of the coating and the decorative panels. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides an antibacterial UV coating and its application in decorative panels, which can improve the antibacterial durability of the UV coating, improve the water and oil resistance of the UV coating, and enhance the bonding strength between the coating and the decorative panel.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0008] An antibacterial UV coating comprises the following raw material components, measured in parts by weight: 40-50 parts of polyurethane acrylate, 42-48 parts of monomers, 1-2 parts of antibacterial composite materials, 5-8 parts of modified polysilazane, and 2-3 parts of photoinitiator.

[0009] The monomer is selected from any one of 1,6-ethylene glycol diacrylate, hydroxyethyl methacrylate, and isobornyl acrylate.

[0010] The photoinitiator is selected from any one of 2-hydroxy-2-methyl-1-phenylpropanone, benzophenone and dimethylacrylamide.

[0011] The method for preparing the antibacterial composite material comprises the following steps: preparing calcium carbonate whiskers, loading the calcium carbonate whiskers with an antibacterial agent, modifying the calcium carbonate whiskers with chitosan, and coating the calcium carbonate whiskers.

[0012] Preparation of the calcium carbonate whisker:

[0013] Dissolve calcium chloride in water, control the pH of the solution to be 6.5-7, add sodium carbonate solution dropwise thereto under stirring, and then place in a water bath at 80-90°C for reaction for 32-36 hours. After the reaction is complete, filter, wash and dry to obtain calcium carbonate whiskers;

[0014] The concentration of the sodium carbonate solution is 33-35wt%;

[0015] The mass ratio of the calcium chloride, sodium carbonate solution and water is 10-15:50-55:100.

[0016] The calcium carbonate whisker loaded antibacterial agent:

[0017] Dissolve cetylpyridinium chloride, allyltrimethylammonium bromide and dodecylbetaine in water, add calcium carbonate whiskers thereto, let stand for 24-28 hours, filter, wash and dry to obtain loaded calcium carbonate whiskers;

[0018] The mass ratio of the cetylpyridinium chloride, allyltrimethylammonium bromide, dodecyl betaine, calcium carbonate whisker and water is 0.5-0.8:0.8-1:0.8-1:20-25:100.

[0019] The chitosan modification:

[0020] Dissolving chitosan in an acetic acid solution to obtain a chitosan solution, dissolving 2,3-epoxypropyltrimethylammonium chloride, 2,5-dihydroxybenzoic acid, and N-hydroxybenzotriazole in a methanol solution to obtain a mixed solution, adding the mixed solution dropwise to the chitosan solution under stirring, controlling the temperature to 55-60° C. to react for 12-15 hours, and obtaining a modified chitosan solution after the reaction is completed;

[0021] The concentration of the acetic acid solution is 1-1.5wt%;

[0022] The mass ratio of chitosan to acetic acid solution is 4-6:200;

[0023] The concentration of the methanol solution is 50-60wt%;

[0024] The mass ratio of the 2,3-epoxypropyltrimethylammonium chloride, 2,5-dihydroxybenzoic acid, N-hydroxybenzotriazole and methanol solution is 0.5-0.8:0.5-0.8:0.3-0.5:50.

[0025] The coating:

[0026] Adding loaded calcium carbonate whiskers and epichlorohydrin to the modified chitosan solution, controlling the temperature to 38-42° C., reacting for 1-1.5 hours under stirring conditions, filtering, washing and drying after the reaction to obtain an antibacterial composite material;

[0027] The mass ratio of the modified chitosan solution, the loaded calcium carbonate whisker and epichlorohydrin is 250:10-15:1-1.5.

[0028] The preparation method of the modified polysilazane is as follows: polysilazane, tridecafluorooctyl triethoxysilane, hexafluorobutyl acrylate, and N,N-dimethylethanolamine are uniformly mixed, and reacted at 80-85° C. for 4-5 hours to obtain the modified polysilazane;

[0029] The mass ratio of the polysilazane, tridecafluorooctyl triethoxysilane, hexafluorobutyl acrylate, and N,N-dimethylethanolamine is 100:5-8:4-6:0.2-0.3;

[0030] The polysilazane is an organic polysilazane with a number average molecular weight of 800-900.

[0031] The viscosity of the polyurethane acrylate is 500-800 cP at 25°C.

[0032] Preparation method of the antibacterial UV coating:

[0033] Weigh the raw material components of the UV coating according to the specified weight proportions, mix the polyurethane acrylate, monomer, antibacterial composite material, modified polysilazane and photoinitiator at a speed of 800-1000 rpm under light-proof and inert protective gas conditions, maintain the temperature at 70-80°C, stir for 1-1.5 hours, and obtain the antibacterial UV coating.

[0034] The antibacterial UV coating is applied to the decorative panel by coating the antibacterial UV coating prepared by the above technical solution on the surface of the decorative panel, wherein the thickness of the antibacterial UV coating is 35-50 μm; after coating, the panel is irradiated with ultraviolet light of 172-365 nm for 2-3 hours;

[0035] The material of the decorative panel is wood.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The antibacterial UV coating of the present invention has excellent antibacterial performance. The antibacterial rates of Escherichia coli and Staphylococcus aureus reach 99.92%-99.99%. It has high antibacterial durability. After 100 hours of ultraviolet light irradiation, the antibacterial rates of Escherichia coli and Staphylococcus aureus are still higher than 95%.

[0038] (2) The antibacterial UV coating of the present invention has high water and oil resistance, with a water contact angle of 122.6°-123.4° and an oil resistance of 99.4%-99.7%.

[0039] (3) The antibacterial UV coating of the present invention has high adhesion strength, and the adhesion on the wood test plate is level 0. DETAILED DESCRIPTION

[0040] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0041] Example 1

[0042] An antibacterial UV coating, comprising the following raw material components, by weight: 40 parts of polyurethane acrylate, 42 parts of monomer, 1 part of antibacterial composite material, 5 parts of modified polysilazane, and 2 parts of photoinitiator;

[0043] 1. Preparation of antibacterial composite materials:

[0044] (1) Preparation of calcium carbonate whiskers: 10 parts of calcium chloride are dissolved in 100 parts of water by weight, the pH of the solution is controlled to be 6.5, 50 parts of 33wt% sodium carbonate solution are added dropwise thereto under stirring, and the mixture is placed in a water bath at 80°C for reaction for 36 hours. After the reaction is completed, the mixture is filtered, washed and dried to obtain calcium carbonate whiskers;

[0045] (2) Calcium carbonate whiskers loaded with antibacterial agent: 0.5 parts of cetylpyridinium chloride, 0.8 parts of allyltrimethylammonium bromide, and 0.8 parts of dodecyl betaine were dissolved in 100 parts of water by weight, and 20 parts of calcium carbonate whiskers were added thereto. After standing for 24 hours, the loaded calcium carbonate whiskers were filtered, washed, and dried to obtain;

[0046] (3) Chitosan modification: 4 parts of chitosan were dissolved in 200 parts of 1 wt% acetic acid solution to obtain a chitosan solution, 0.5 parts of 2,3-epoxypropyltrimethylammonium chloride, 0.8 parts of 2,5-dihydroxybenzoic acid, and 0.3 parts of N-hydroxybenzotriazole were dissolved in 50 parts of 50 wt% methanol solution to obtain a mixed solution, and the mixed solution was added dropwise to the chitosan solution under stirring, and the temperature was controlled to 55°C for 15 hours to obtain a modified chitosan solution after the reaction was completed;

[0047] (4) Coating: According to the weight ratio, 10 parts of loaded calcium carbonate whiskers and 1 part of epichlorohydrin were added to 250 parts of modified chitosan solution, and the temperature was controlled to 38°C. The mixture was reacted for 1.5 hours under stirring. After the reaction, the mixture was filtered, washed and dried to obtain an antibacterial composite material.

[0048] 2. Preparation of modified polysilazane: According to weight parts, 100 parts of polysilazane, 5 parts of tridecafluorooctyl triethoxysilane, 4 parts of hexafluorobutyl acrylate, and 0.2 parts of N,N-dimethylethanolamine were added into a reactor and mixed evenly, and reacted at 80° C. for 5 hours to obtain modified polysilazane;

[0049] The polysilazane is an organic polysilazane with a number average molecular weight of 800-900.

[0050] The viscosity of the polyurethane acrylate is 500-800 cP at 25°C;

[0051] The monomer is 1,6-ethylene glycol diacrylate;

[0052] The photoinitiator is 2-hydroxy-2-methyl-1-phenylpropanone.

[0053] Preparation method of the antibacterial UV coating:

[0054] Weigh the raw material components of the UV coating according to the specified weight proportions, mix the polyurethane acrylate, monomer, antibacterial composite material, modified polysilazane and photoinitiator at 800 rpm under light-proof and inert protective gas conditions, maintain the temperature at 70°C, stir for 1.5 hours, and obtain the antibacterial UV coating.

[0055] This embodiment also provides the application of antibacterial UV coating in decorative panels, specifically: the antibacterial UV coating prepared by the preparation method described in the above technical solution is applied to the surface of the decorative panel, and the thickness of the antibacterial UV coating is 35 μm; after coating, 172 nm ultraviolet light is used for irradiation for 2 hours;

[0056] The material of the decorative panel is wood.

[0057] Example 2

[0058] An antibacterial UV coating, comprising the following raw material components, by weight: 45 parts of polyurethane acrylate, 45 parts of monomer, 1.5 parts of antibacterial composite material, 6 parts of modified polysilazane, and 2.5 parts of photoinitiator;

[0059] 1. Preparation of antibacterial composite materials:

[0060] (1) Preparation of calcium carbonate whiskers: 12 parts of calcium chloride are dissolved in 100 parts of water by weight, the pH of the solution is controlled to be 6.7, 52 parts of 34 wt% sodium carbonate solution are added dropwise thereto under stirring, and the mixture is placed in a water bath at 85° C. for reaction for 34 h. After the reaction is completed, the mixture is filtered, washed and dried to obtain calcium carbonate whiskers;

[0061] (2) Calcium carbonate whiskers loaded with antibacterial agent: 0.6 parts of cetylpyridinium chloride, 0.9 parts of allyltrimethylammonium bromide, and 0.9 parts of dodecyl betaine were dissolved in 100 parts of water by weight, and 22 parts of calcium carbonate whiskers were added thereto. After standing for 26 hours, the loaded calcium carbonate whiskers were filtered, washed, and dried to obtain;

[0062] (3) Chitosan modification: 5 parts of chitosan were dissolved in 200 parts of 1.2 wt% acetic acid solution to obtain a chitosan solution, 0.6 parts of 2,3-epoxypropyltrimethylammonium chloride, 0.7 parts of 2,5-dihydroxybenzoic acid, and 0.4 parts of N-hydroxybenzotriazole were dissolved in 50 parts of 55 wt% methanol solution to obtain a mixed solution, and the mixed solution was added dropwise to the chitosan solution under stirring, and the temperature was controlled to 58°C for 13 hours to obtain a modified chitosan solution after the reaction was completed;

[0063] (4) Coating: According to the weight ratio, 13 parts of loaded calcium carbonate whiskers and 1.3 parts of epichlorohydrin were added to 250 parts of modified chitosan solution, and the temperature was controlled to 40°C. The mixture was reacted for 12 hours under stirring. After the reaction, the mixture was filtered, washed and dried to obtain an antibacterial composite material.

[0064] 2. Preparation of modified polysilazane: According to weight parts, 100 parts of polysilazane, 6 parts of tridecafluorooctyl triethoxysilane, 5 parts of hexafluorobutyl acrylate, and 0.25 parts of N,N-dimethylethanolamine were added into a reactor and mixed evenly, and reacted at 82° C. for 4.5 hours to obtain modified polysilazane;

[0065] The polysilazane is an organic polysilazane with a number average molecular weight of 800-900.

[0066] The viscosity of the polyurethane acrylate is 500-800 cP at 25°C;

[0067] The monomer is hydroxyethyl methacrylate;

[0068] The photoinitiator is benzophenone.

[0069] Preparation method of the antibacterial UV coating:

[0070] Weigh the raw material components of the UV coating according to the specified weight proportions, mix the polyurethane acrylate, monomer, antibacterial composite material, modified polysilazane and photoinitiator at 900 rpm under light-proof and inert protective gas conditions, maintain the temperature at 75°C, stir for 1.2 hours, and obtain the antibacterial UV coating.

[0071] This embodiment also provides the application of antibacterial UV coating in decorative panels, specifically: the antibacterial UV coating prepared by the preparation method described in the above technical solution is applied to the surface of the decorative panel, and the thickness of the antibacterial UV coating is 40 μm; after coating, 254 nm ultraviolet light is used for irradiation for 2.5 hours;

[0072] The material of the decorative panel is wood.

[0073] Example 3

[0074] An antibacterial UV coating, comprising the following raw material components, by weight: 50 parts of polyurethane acrylate, 48 parts of monomer, 2 parts of antibacterial composite material, 8 parts of modified polysilazane, and 3 parts of photoinitiator;

[0075] 1. Preparation of antibacterial composite materials:

[0076] (1) Preparation of calcium carbonate whiskers: 15 parts of calcium chloride are dissolved in 100 parts of water by weight, the pH of the solution is controlled to be 7, 55 parts of a 35 wt% sodium carbonate solution are added dropwise thereto under stirring, and the mixture is placed in a 90° C. water bath for reaction for 36 hours. After the reaction is completed, the mixture is filtered, washed and dried to obtain calcium carbonate whiskers;

[0077] (2) Calcium carbonate whiskers loaded with antibacterial agent: 0.8 parts of cetylpyridinium chloride, 1 part of allyltrimethylammonium bromide, and 1 part of dodecyl betaine were dissolved in 100 parts of water by weight, and 25 parts of calcium carbonate whiskers were added thereto. After standing for 28 hours, the loaded calcium carbonate whiskers were filtered, washed, and dried to obtain;

[0078] (3) Chitosan modification: 6 parts of chitosan were dissolved in 200 parts of 1.5wt% acetic acid solution to obtain a chitosan solution, 0.8 parts of 2,3-epoxypropyltrimethylammonium chloride, 0.8 parts of 2,5-dihydroxybenzoic acid, and 0.5 parts of N-hydroxybenzotriazole were dissolved in 50 parts of 60wt% methanol solution to obtain a mixed solution, and the mixed solution was added dropwise to the chitosan solution under stirring, and the temperature was controlled to 60°C for 12 hours to obtain a modified chitosan solution after the reaction was completed;

[0079] (4) Coating: According to the weight ratio, 15 parts of loaded calcium carbonate whiskers and 1.5 parts of epichlorohydrin were added to 250 parts of modified chitosan solution, and the temperature was controlled to 42°C. The mixture was reacted for 1 hour under stirring. After the reaction, the mixture was filtered, washed and dried to obtain an antibacterial composite material.

[0080] 2. Preparation of modified polysilazane: According to weight parts, 100 parts of polysilazane, 8 parts of tridecafluorooctyl triethoxysilane, 6 parts of hexafluorobutyl acrylate, and 0.3 parts of N,N-dimethylethanolamine were added into a reactor and mixed evenly, and reacted at 85° C. for 4 hours to obtain modified polysilazane;

[0081] The polysilazane is an organic polysilazane with a number average molecular weight of 800-900.

[0082] The viscosity of the polyurethane acrylate is 500-800 cP at 25°C;

[0083] The monomer is isobornyl acrylate;

[0084] The photoinitiator is dimethyl acrylamide.

[0085] Preparation method of the antibacterial UV coating:

[0086] Weigh the raw material components of the UV coating according to the specified weight proportions, mix the polyurethane acrylate, monomer, antibacterial composite material, modified polysilazane and photoinitiator at a speed of 1000 rpm under light-proof and inert protective gas conditions, maintain the temperature at 80°C, stir for 1 hour, and obtain the antibacterial UV coating.

[0087] This embodiment also provides the application of antibacterial UV coating in decorative panels, specifically: the antibacterial UV coating prepared by the preparation method described in the above technical solution is applied to the surface of the decorative panel, and the thickness of the antibacterial UV coating is 50 μm; after coating, 365 nm ultraviolet light is used for irradiation for 3 hours;

[0088] The material of the decorative panel is wood.

[0089] Comparative Example 1

[0090] Comparative Example 1 uses the antibacterial UV coating described in Example 2, the difference being that in the step of preparing the antibacterial composite material, the chitosan modification and coating steps are omitted, and the prepared loaded calcium carbonate whisker is the antibacterial composite material, and the remaining steps are the same.

[0091] Comparative Example 2

[0092] Comparative Example 2 uses the antibacterial UV coating described in Example 2, except that in the step of preparing the antibacterial composite material, the step of loading the calcium carbonate whisker with the antibacterial agent is omitted, and in the coating step, calcium carbonate whiskers are used instead of loaded calcium carbonate whiskers, and the remaining steps are the same.

[0093] Comparative Example 3

[0094] Comparative Example 3 uses the antibacterial UV coating described in Example 2, except that the step of preparing the modified polysilazane is omitted, and in the step of preparing the antibacterial UV coating, polysilazane is used instead of the modified polysilazane, and the remaining steps are the same.

[0095] Test Example 1

[0096] The antibacterial UV coatings prepared in Examples 1-3 and Comparative Examples 1-3 were tested for their antibacterial durability. The testing method was as follows: an antibacterial coating test plate was prepared according to HG / T 3950-2007, and a 30W ultraviolet lamp with a wavelength of 253.7nm was used. The ultraviolet lamp complied with GB19258 standard. The antibacterial coating test plate was 1.0m away from the ultraviolet lamp and irradiated for 0h, 5h, 20h, 50h, and 100h. The antibacterial performance of the treated test plate was tested according to Appendix A Antibacterial Coatings - Antibacterial Performance Test Method of HG / T 3950-2007. The antibacterial rate of Escherichia coli and the antibacterial rate of Staphylococcus aureus were tested. The test results are shown in Table 1.

[0097] Table 1

[0098]

[0099] It can be seen from Table 1 that the antibacterial rates of Escherichia coli and Staphylococcus aureus of the UV coating of Example 2 reached 99.99% and 99.93%, respectively, and have excellent antibacterial properties; the antibacterial rates of Escherichia coli and Staphylococcus aureus of the UV coating only decreased slightly with the increase of ultraviolet lamp irradiation time, and after 100 hours of ultraviolet lamp irradiation, the antibacterial rates of Escherichia coli and Staphylococcus aureus were still above 95%, and the antibacterial and long-lasting performance was good.

[0100] The calcium carbonate whisker prepared by the present invention has a hollow structure under specific conditions, and three antibacterial agents, namely, cetylpyridinium chloride, allyltrimethylammonium bromide and dodecyl betaine, are loaded by adsorption, and modified chitosan is coated on the surface of the calcium carbonate whisker. The surface coating of the calcium carbonate whisker can avoid the large-scale release of the antibacterial agent in a short time after the UV coating is applied, greatly delay the sustained release time of the antibacterial agent, and increase the antibacterial durability of the UV coating.

[0101] The modified chitosan coated on the surface of the calcium carbonate whisker is prepared by modifying chitosan with 2,3-epoxypropyltrimethylammonium chloride, 2,5-dihydroxybenzoic acid and N-hydroxybenzotriazole, so that the modified chitosan has higher antibacterial property and improves the antibacterial property of the UV coating.

[0102] After polysilazane is modified with tridecafluorooctyltriethoxysilane and hexafluorobutyl acrylate, the surface energy of polysilazane is reduced. The coating to which modified polysilazane is added not only increases the hardness of the coating, but also reduces the surface energy of the coating after curing, thereby improving the water and oil resistance of the coating, making it impossible for bacteria to grow, and can improve the antibacterial property of the coating to a certain extent.

[0103] The antibacterial rates of Escherichia coli and Staphylococcus aureus of the UV coating of Comparative Example 1 remained above 90% within the first 5 hours of ultraviolet light irradiation, while the antibacterial rates of Escherichia coli and Staphylococcus aureus tested after 20 hours of ultraviolet light irradiation dropped significantly. This is because the antibacterial composite material prepared by omitting the chitosan modification and coating steps lacks the coating of modified chitosan. After a period of ultraviolet light irradiation, the antibacterial composite material will experience a burst release of antibacterial agents. The initial burst release is too high, resulting in insufficient concentration of subsequent antibacterial agent release and a significant decrease in antibacterial properties.

[0104] The antibacterial rates of Escherichia coli and Staphylococcus aureus of the UV coating of Comparative Example 2 were lower than those of Example 2 when not irradiated by ultraviolet light, and the antibacterial rates of Escherichia coli and Staphylococcus aureus decreased with the increase of ultraviolet light irradiation time. In the step of loading the antibacterial agent with calcium carbonate whiskers in Comparative Example 2, the coating lacked the sustained release performance of the antibacterial agent, and the modified chitosan on the surface of the coating decreased significantly with the irradiation time of the ultraviolet light. The antibacterial performance of the coating decreased linearly.

[0105] The antibacterial rates of Escherichia coli and Staphylococcus aureus of the UV coating of Comparative Example 3 are slightly lower than those of Example 2. The antibacterial rates of Escherichia coli and Staphylococcus aureus decrease slightly with the increase of UV lamp irradiation time. The antibacterial rates of Escherichia coli and Staphylococcus aureus tested after 100 hours of UV lamp irradiation are lower than those of Example 2. Comparative Example 3 omits the modification of polysilazane, which reduces the water and oil resistance of the coating surface, resulting in a decrease in the antibacterial performance of the coating.

[0106] Test Example 2

[0107] The antibacterial UV coatings prepared in Examples 1-3 and Comparative Example 3 were tested for water contact angle, oil resistance, and adhesion. The adhesion was tested according to GB / T 9286-2021, where the test plate was made of wood; the oil resistance was tested using a black oily marker pen, which was applied to the surface of the coating. After five minutes, it was wiped with a dry cloth or a paper towel that complies with GB20810-2006, and the reflection coefficient of the coating was tested with a reflectivity meter. The ratio of the reflection coefficient of the test area after the black oily marker test to the initial reflection coefficient of the test area is the oil resistance; the test results are shown in Table 2.

[0108] Table 2

[0109]

[0110] It can be seen from Table 2 that the water contact angle, oil resistance and adhesion of Comparative Example 3 are significantly lower than those of Example 2. After the polysilazane is modified with tridecafluorooctyltriethoxysilane and hexafluorobutyl acrylate, the surface energy of the polysilazane is reduced, the water contact angle and oil resistance are improved, and the adhesion of the coating is improved.

[0111] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An antibacterial UV coating, characterized in that: The antibacterial UV coating is composed of the following raw material components, in parts by weight: 40-50 parts of polyurethane acrylate, 42-48 parts of monomer, 1-2 parts of antibacterial composite material, 5-8 parts of modified polysilazane, and 2-3 parts of photoinitiator; The monomer is selected from any one of 1,6-ethylene glycol diacrylate, hydroxyethyl methacrylate, and isobornyl acrylate; The preparation method of the modified polysilazane is as follows: polysilazane, tridecafluorooctyl triethoxysilane, hexafluorobutyl acrylate, and N,N-dimethylethanolamine are uniformly mixed, and reacted at 80-85° C. for 4-5 hours to obtain the modified polysilazane; The method for preparing the antibacterial composite material comprises the following steps: preparation of calcium carbonate whiskers, loading of calcium carbonate whiskers with an antibacterial agent, chitosan modification and coating steps; The preparation method of the calcium carbonate whisker comprises the following steps: dissolving calcium chloride in water, controlling the pH value of the solution to be 6.5-7, dripping a sodium carbonate solution thereinto under stirring, and then placing the solution in a water bath at 80-90° C. for reaction for 32-36 hours. After the reaction is completed, the solution is filtered, washed and dried to obtain the calcium carbonate whisker. The method for loading the calcium carbonate whisker with an antibacterial agent comprises dissolving cetylpyridinium chloride, allyltrimethylammonium bromide and dodecyl betaine in water, adding the calcium carbonate whisker thereto, standing for 24-28 hours, filtering, washing and drying to obtain the loaded calcium carbonate whisker; The chitosan modification method comprises dissolving chitosan in an acetic acid solution to obtain a chitosan solution, dissolving 2,3-epoxypropyltrimethylammonium chloride, 2,5-dihydroxybenzoic acid, and N-hydroxybenzotriazole in a methanol solution to obtain a mixed solution, adding the mixed solution dropwise to the chitosan solution under stirring, controlling the temperature to 55-60° C. to react for 12-15 hours, and obtaining a modified chitosan solution after the reaction is completed; The coating method comprises adding loaded calcium carbonate whiskers and epichlorohydrin to the modified chitosan solution, controlling the temperature to 38-42° C., reacting for 1-1.5 hours under stirring conditions, filtering, washing and drying after the reaction to obtain an antibacterial composite material.

2. The antibacterial UV coating according to claim 1, characterized in that: The mass ratio of the polysilazane, tridecafluorooctyl triethoxysilane, hexafluorobutyl acrylate and N,N-dimethylethanolamine is 100:5-8:4-6:0.2-0.

3.

3. The antibacterial UV coating according to claim 1, characterized in that: In the preparation step of the calcium carbonate whisker, the concentration of the sodium carbonate solution is 33-35wt%; the mass ratio of calcium chloride, sodium carbonate solution and water is 10-15:50-55:

100.

4. The antibacterial UV coating according to claim 1, characterized in that: In the step of loading the calcium carbonate whisker with an antibacterial agent, the mass ratio of cetylpyridinium chloride, allyltrimethylammonium bromide, dodecyl betaine, calcium carbonate whisker and water is 0.5-0.8:0.8-1:0.8-1:20-25:

100.

5. The antibacterial UV coating according to claim 1, characterized in that: In the step of modifying chitosan, The concentration of the acetic acid solution is 1-1.5wt%; the mass ratio of the chitosan to the acetic acid solution is 4-6:200; The concentration of the methanol solution is 50-60wt%; The mass ratio of the 2,3-epoxypropyltrimethylammonium chloride, 2,5-dihydroxybenzoic acid, N-hydroxybenzotriazole and methanol solution is 0.5-0.8:0.5-0.8:0.3-0.5:

50.

6. The antibacterial UV coating according to claim 1, characterized in that: In the coating step, the mass ratio of the modified chitosan solution, the loaded calcium carbonate whiskers and epichlorohydrin is 250:10-15:1-1.

5.

7. The antibacterial UV coating according to claim 1, characterized in that: The photoinitiator is selected from any one of 2-hydroxy-2-methyl-1-phenylpropanone, benzophenone and dimethylacrylamide.

8. Use of the antibacterial UV coating according to any one of claims 1 to 7 in decorative panels, characterized in that: The antibacterial UV coating is applied to the surface of the decorative panel, the thickness of the antibacterial UV coating is 35-50 μm, and after coating, it is irradiated with ultraviolet light of 172-365 nm for 2-3 hours.

Citation Information

Patent Citations

  • Antimicrobial UV coating and making process thereof

    CN101338087B

  • Antibacterial coating for interior decoration and preparation method thereof

    CN112574608A

  • Preparation of polystyrene sustained-release microcapsules for embedding sodium benzoate sea anti-fouling agent

    CN102086291A

  • Chemical / ionic / physical compounding cross linking hydrogel and preparation method thereof

    CN102911381A